Does Performance Evaluation Mattered? An Explanation from Literature Study - Aryan Danil Mirza. BR; Fitri Mareta (Pusat P2M Politeknik Negeri Batam, 2023)
Performance evaluation aims to improve human resources to accelerate the achievement of organizational goals. This systematic review identifies individual performance evaluation indicators and builds a reliable information system based on errors in evaluating performance. This research is qualitative. This research uses secondary data using a literature study approach. A systematic literature search was conducted for peer-reviewed articles published from 1991 to 2022 that discussed performance evaluation. Bibliographical databases include Science Direct, Emerald, JSTOR, and Osiris. Articles must identify individual performance appraisal factors and errors in performance evaluation. The results identify that the organization carries out performance evaluations aimed at reviewing individual performance to determine each individual's potential so that it can be adjusted to the organization's reward and punishment standards. However, several individual performance appraisal factors and errors in a performance evaluation that have important implications for practice are caused by the hello effect, horns effect, central tendency, and strictness and leniency. This study has several limitations because this review covers a range of performance evaluation topics, ignoring many other papers that could provide meaningful insights. Further research can expand the topic of discussion related to performance evaluation indicators, especially in Indonesia. In addition, this review explicitly discusses performance evaluation in the private sector. Further research can specifically discuss public sector performance evaluation so that it has an impact on improving public sector performance and encouraging Good Corporate Governance (GCG).